Characteristics and comorbidities of inpatients without celiac disease on a gluten-free diet. Issue 4 (April 2018) - Blackett, John W.; Shamsunder, Meghana; Reilly, Norelle R.; Green, Peter H.R.; Lebwohl, Benjamin
Abstract : Objectives: Despite the increasing popularity of gluten-free diet (GFD), the demographic characteristics and medical features of patients without celiac disease on this diet have not been extensively investigated. We aimed to characterize the medical conditions and demographic backgrounds of hospitalized patients without celiac disease who adhere to a GFD, to further understand their reasons for gluten avoidance. Materials and methods: We performed an observational cohort study on all inpatients at Columbia University Medical Center on a GFD in 2011–2016, excluding those with celiac disease, compared with age-matched and sex-matched inpatients on a regular diet. We determined the odds ratio (OR) of being on a GFD for various comorbidities using conditional logistic regression. Results: Of 769 inpatients on a GFD, most (63.6%) did not have celiac disease. Gluten-avoiding patients were more likely to be non-Hispanic Whites [OR: 2.92; 95% confidence interval (CI): 2.31–3.70]. They had a lower prevalence of hypertension (OR: 0.38; 95% CI: 0.27–0.52) and diabetes (OR: 0.58; 95% CI: 0.32–0.75) and higher prevalence of inflammatory bowel disease (OR: 1.56; 95% CI: 1.02–2.41), irritable bowel syndrome (OR: 6.16; 95% CI: 2.11–10.23), hyperthyroidism (OR: 2.73; 95% CI: 1.22–6.10), hypothyroidism (OR: 2.06; 95% CI: 1.39–3.06), lupus (OR: 2.87; 95% CI: 1.13–7.29), and autism spectrum disorder (OR: 23.42; 95% CI: 5.29–103.73). Conclusion: Nonceliac gluten-avoiding patients have higher prevalences of inflammatory bowel disease, irritable bowel syndrome, thyroid disease, lupus, and autism spectrum disorder, suggesting patients with these disorders have turned to a GFD for perceived benefit, despite a scant evidence basis.